Practica 2
Practica 2
Practica 2
a) 2x-3x2-x-2
AX-2+BX+1=2x-3x2-x-2 →A=-13 B=53
-13X-2dx+53x+1dx=-13.lnx-2+53lnx+1
→2x-3x2-x-2=-13.lnx-2+ 53lnx+1+c
b) xx+12x+1dx
xx+12x+1=Ax+1+B2x+1
1x+1dx+12.-1.22x+1dx=lnx+1-ln2x+1
xx+12x+1dx= lnx+1-ln2x+1+c
c)2x+7x2-3x-10dx
177x-5dx+-37x+2 dx=177lnx-5-37lnx+2
2x+7x2-3x-10dx=177lnx-5-37lnx+2+c
d)x5+x4-8x3-4xdx
x5+x4-8x3-4x=x2+x+4+4x2+16x-8xx-2(x+2)
x2+x+4+2X+5X-2-3X+2=x33+ x22+4x+2lnx+5lnx-2-3lnx+2
x5+x4-8x3-4xdx=x33+ x22+4x+2lnx+5lnx-2-3lnx+2+c
e)x(x-1)(x+3)(x+5)dx
124x-1+38x+3+-512X+5=124lnx-1+38lnx+3-512lnx+5
xx-1x+3x+5dx=124lnx-1+38lnx+3-512lnx+5+c
f)2x2+41x-91x-1x+3x-4dx
(4x-1+-7X+3+5X-4)dx=4lnx-1-7lnx+3+5lnx-4
2x2+41x-91x-1x+3x-4dx=4lnx-1-7lnx+3+5lnx-4+c
g) dxx2-1(x2-5x+6)
14X-1+-124X+1+18X-3+-13X-2dx=14lnx-1-124lnx+1+18lnx-3-13x-2
dxx2-1(x2-5x+6)=14lnx-1-124lnx+1+18lnx-3-13x-2+c
h) 32x2x-1(4x2-16x+15)dx
(22x-1+-122x-3+102x-5)dx=ln2x-1-6ln2x-3+5ln2x-5
32x2x-14x2-16x+15dx= ln2x-1-6ln2x-3+5ln2x-5+c
i)4x2-x-8x3-x2-2xdx
(4x+-1x+1+1x-2)dx=4lnx-lnx+1+lnx-2
4x2-x-8x3-x2-2xdx=4lnx-lnx+1+lnx-2+c
j)2x2-5x4-5x2+6
(-24x+2+24x-2+-36x+3+36x-3)dx=-24lnx+2+24lnx-2-36lnx+3+36lnx-3
2x2-5x4-5x2+6=-24lnx+2+24lnx-2-36lnx+3+36lnx-3+c
a)2x-1x-13dx
(2x-12+1x-13)=-2X-1-12(x-1)2
2x-1x-13dx=-2X-1-12.1(x-1)2+c
b)x2-3x+2x(x2+2x+1)dx
2x-1x+1-6x+12dx=2lnx-lnx+1+6x+1
x2-3x+2x(x2+2x+1)dx=2lnx-lnx+1+6x+1+c
c)x2x3+5x2+8x+4
x2x3+5x2+8x+4=Ax+1+Bx+2+C(x+2)2
1x+1-4x+22dx=lnx+1+4x+2
x2x3+5x2+8x+4=lnx+1+4x+2+c
d)3x4-x2+1(x-1)5
3x4-x2+1(x-1)5=AX-1+B(x-1)2+C(x-1)3+D(x-1)4+E(x-1)5
3x4-x2+1=Ax-14+Bx-13+Cx-12+Dx-1+E
al reemplazar x=1 se obtiene E=3 luego para X=2, X=0, X=-1, X=3 se
obtine un sistema de ecuaciones resolviendo ese sistema
(3X-1+12(x-1)2+17(x-1)3+10(x-1)4+3(x-1)5)dx=3lnx-1-12x-1-172(x-1)2-
103(x-1)3-34(x-1)4
3x4-x2+1(x-1)5=3lnx-1-12x-1-172.1(x-1)2-103.1(x-1)3-34.1(x-1)4+c
e)x3-6x2+11x-5x-24dx
x3-6x2+11x-5x-24=Ax-2+Bx-22+Cx-23+Dx-24
1x-2+-1x-23+1x-24dx=lnx-2+12.1(x-2)2-13.1(x-2)3
x3-6x2+11x-5x-24dx=lnx-2+12.1(x-2)2-13.1(x-2)3+c
f)x2+1x3+9x2+27x+27dx
x2+1x3+9x2+27x+27=Ax+3+B(x+3)2+C(x+3)3
1x+3-6(x+3)2+10(x+3)3dx=lnx+3+6x+3-5(x+3)2
x2+1x3+9x2+27x+27dx= lnx+3+6x+3-5(x+3)2+c
g)1x4-x2dx
-1x2+12x-1+-12x+1dx
1x4-x2dx=1x+12.lnx-1-12.lnx+1+c
h)x2x+22x+42dx
x2x+22x+42=Ax+2+Bx+22+Cx+4+Dx+42
x2=Ax+42x+2+Bx+42+Cx+4x+22+Dx+22
RESOLVIENDO A=-2, B=1, C=2, D=4
-2x+2+1x+22+2x+4+4x+42dx
x2x+22x+42dx=-2lnx+2+2lnx+4-1x+2-4x+4+C
i)x-1x3+2x2+xdx
x-1x3+2x2+x=Ax+Bx+1+C(x+1)2
-1x+1x+1+2(x+1)2dx
x-1x3+2x2+xdx=-lnx+lnx+1-2x+1+C
j)x3-2x2+4x3(x-2)2dx
x3-2x2+4x3x-22=Ax+Bx2+CX3+Dx-2+Ex-22
x3-2x2+4=Ax2x-22+Bxx-22+Cx-22+Dx3x-2+Ex3
RESOLVIENDO A=1/4 B=1, C=1 D=-1/4 E=1/2
14x+1x2+1X3+-14x-2+12x-22dx
x3-2x2+4x3(x-2)2dx=14lnx-1x-12.1x2-14lnx-2-12.1x-2+c
B) 3x-4x-2(x2+3x-1)dx
Solución:
3x-4x-2(x2+3x-1)=A(x-2)+Bx+C(x2+3x-1)
3x-4=Ax2+3x-1+Bx2-2x+C(x-2)
3x-4=x2A+B+x3A-2B+C+(-A-2C)
A+B=0
3A-2B+C=3
-A-2C=-4
A=29, B=-29, C=179
3x-4x-2(x2+3x-1)dx=29dx(x-2)-192x-17(x2+3x-1)dx
3x-4x-2(x2+3x-1)dx=29lnx-2-192x+3-20(x2+3x-1)dx
3x-4x-2(x2+3x-1)dx=29lnx-2-192x+3x2+3x-1dx+209dx(x2+3x-1)
3x-4x-2(x2+3x-1)dx=29lnx-2-19lnx2+3x-1+209dx(x+32)2-(134)2
3x-4x-2(x2+3x-1)dx=29lnx-2-19lnx2+3x-1+20912413lnx+32-
134x+32+134+C
3x-4x-2(x2+3x-1)dx=29lnx-2-19lnx2+3x-1+20913ln2x+3-
132x+3+13+C
C) x2(1-x4)dx
Solución:
x2(1-x4)dx=-x2x+1x-1(x2+1)dx
x2x+1x-1(x2+1)=A(x+1)+B(x-1)+Cx+D(x2+1)
x2=Ax3-x2+x-1+Bx3+x2+x+1+Cx3-x+D(x2-1)
x2=x3A+B+C+x2-A+B+D+xA+B-C+(-A+B-D)
A+B+C=0
-A+B+D=1
A+B-C=0
-A+B-D=0
A=-14, B=14, C=0, D=12
x2(1-x4)dx=--14dx(x+1)+14dx(x-1)+12dxx2+1
x2(1-x4)dx=14dx(x+1)-14dx(x-1)-12dxx2+1
x2(1-x4)dx=14lnx+1-14lnx-1-1211arctgx1+C
x2(1-x4)dx=14lnx+1-14lnx-1-12arctgx+C
D) xx6-1dx
Solución:
xx6-1dx=xx+1x2-x+1x-1(x2+x+1)dx
xx+1x2-x+1x-1(x2+x+1)=A(x+1)+Bx+Cx2-x+1+Dx-
1+Ex+F(x2+x+1)
x=Ax5-x4+x3-x2+x-1+Bx5+x4-x2-x+Cx4+x3-x-
1+Dx5+x4+x3+x2+x+1+Ex5-x4+x2-x+F(x4-x3+x-1)
x=x5A+B+D+E+x4-A+B+C+D-E+F+x3A+C+D-F+x2-A-B+D+E+xA-
B-C+D-E+F+(-A-C+D-F)
A+B+D+E=0
-A+B+C+D-E+F=0
A+C+D-F=0
-A-B+D+E=0
A-B-C+D-E+F=1
-A-C+D-F=0
A=16, B=-16, C=-16, D=16, E=-16, F=16
xx6-1dx=16dx(x+1)-16x+1x2-x+1dx+16dx(x-1)-16x-1(x2+x+1)dx
xx6-1dx=16lnx+1-1122x+2x2-x+1dx+16lnx-1-1122x-2(x2+x+1)dx
xx6-1dx=16lnx+1-1122x-1+3x2-x+1dx+16lnx-1-1122x+1-
3(x2+x+1)dx
xx6-1dx=16lnx+1-1122x-1x2-x+1dx-14dxx2-x+1+16lnx-1-
1122x+1(x2+x+1)dx+14dx(x2+x+1)
xx6-1dx=16lnx+1-112lnx2-x+1-123arctg2x-13+16lnx-1-
112lnx2+x+1+123arctg(2x+13)
E) dxx+12(x2+1)dx
Solución:
1x+12(x2+1)=A(X+1)+Bx+12+Cx+D(x2+1)
1=Ax3+x2+x+1+Bx2+1+Cx3+2x2+x+D(x2+2x+1)
1=x3A+C+x2A+B+2C+D+xA+C+2D+(A+B+D)
A+C=0
A+B+2C+D=0
A+C+2D=0
A+B+D=1
A=12, B=12, C=-12, D=0
dxx+12(x2+1)dx=12dx(x+1)+12dx(x+1)2-12xx2+1dx
dxx+12(x2+1)dx=12lnx+1-12(x+1)-12122xx2+1dx
dxx+12(x2+1)dx=12lnx+1-12(x+1)-14lnx2+1+C
F) x5+2x3+4x+4x4+2x3+2x2dx
Solución:
x5+2x3+4x+4x4+2x3+2x2dx=x-2+4x3+4x2+4x+4x4+2x3+2x2dx
x5+2x3+4x+4x4+2x3+2x2dx=(x-
2)dx+4x3+4x2+4x+4x2(x2+2x+2)dx
4x3+4x2+4x+4x2(x2+2x+2)=Ax+Bx2+Cx+Dx2+2x+2
4x3+4x2+4x+4=Ax3+2x2+2x+Bx2+2x+2+Cx3+D(x2)
4x3+4x2+4x+4=x3A+C+x22A+B+D+x2A+2B+(2B)
A+C=4
2A+B+D=4
2A+2B=4
2B=4
A=2, B=2, C=2, D=-2
x5+2x3+4x+4x4+2x3+2x2dx=(x-
2)dx+4x3+4x2+4x+4x2(x2+2x+2)dx
x5+2x3+4x+4x4+2x3+2x2dx=x22-2x+2dxx+2dxx2+2x-
2x2+2x+2dx
x5+2x3+4x+4x4+2x3+2x2dx=x22-2x+2lnx-2x+2x+2-4x2+2x+2dx
x5+2x3+4x+4x4+2x3+2x2dx=x22-2x+2lnx-2x+2x+2x2+2x+2dx-
4dxx2+2x+2
x5+2x3+4x+4x4+2x3+2x2dx=x22-2x+2lnx-2x+lnx2+2x+2-
4dx(x+1)2+(1)2
x5+2x3+4x+4x4+2x3+2x2dx=x22-2x+2lnx-2x+lnx2+2x+2-
4arctgx+1+C
G) 3x2+3x+1x3+2x2+2x+1dx
Solución:
3x2+3x+1x3+2x2+2x+1dx=3x2+3x+1x+1(x2+x+1)dx
3x2+3x+1x+1(x2+x+1)=A(x+1)+Bx+C(x2+x+1)
3x2+3x+1=Ax2+x+1+Bx2+x+C(x+1)
3x2+3x+1=x2A+B+xA+B+C+(A+C)
A+B=3
A+B+C=3
A+C=1
A=1, B=2, C=0
3x2+3x+1x3+2x2+2x+1dx=1dx(x+1)+2x(x2+x+1)dx
3x2+3x+1x3+2x2+2x+1dx=lnx+1+2x+1-1(x2+x+1)dx
3x2+3x+1x3+2x2+2x+1dx=lnx+1+2x+1(x2+x+1)dx-dx(x2+x+1)
3x2+3x+1x3+2x2+2x+1dx=lnx+1+lnx2+x+1-dx(x+12)2+(34)2
3x2+3x+1x3+2x2+2x+1dx=lnx+1+lnx2+x+1-23arctg2x+13+C
H) 2x2+x+1x2+3(2x2+x+5)dx
Solución:
2x2+x+1x2+3(2x2+x+5)=Ax+Bx2+3+Cx+D(2x2+x+5)
2x2+x+1=A2x3+x2+5x+B2x2+x+5+Cx3+3x+D(x2+3)
2x2+x+1=x32A+C+x2A+2B+D+x5A+B+3C+(5B+3D)
2A+C=0
A+2B+D=2
5A+B+3C=1
5B+3D=1
A=1, B=2, C=-2, D=-3
2x2+x+1x2+3(2x2+x+5)dx=x+2(x2+3)dx-2x+32x2+x+5dx
2x2+x+1x2+3(2x2+x+5)dx=122x+4x2+3dx-124x+62x2+x+5dx
2x2+x+1x2+3(2x2+x+5)dx=122xx2+3dx+2dxx2+3-
124x+1+52x2+x+5dx
2x2+x+1x2+3(2x2+x+5)dx=12lnx2+3+213arctgx3-
124x+12x2+x+5dx-53dx2x2+x+5
2x2+x+1x2+3(2x2+x+5)dx=12lnx2+3+213arctgx3-12ln2x2+x+5-
52dx(2x+122)2+(398)2
2x2+x+1x2+3(2x2+x+5)dx=12lnx2+3+213arctgx3-12ln2x2+x+5-
5239arctg4x+139+C
a)3x(x2+x+3)3dx
3xx2+x+33dx=3x(x+122+1122)3dx
3(112tan∝-12)112 (sec∝)2d∝(114(sec∝)2)3
3114tan∝(sec∝)2d∝(114(sec∝)2)3-3114(sec∝)2d∝(114(sec∝)2)3
3tan∝sec∝d∝1214sec∝5-
b)1(X3-1)2dx
1(X3-1)2=AX-1+B(X-1)2+C2x+1+D(x2+x+1)+E2X+1+F(x2+x+1)2
(-29X-1+19(X-1)2+192x+1+29(x2+x+1)+162X+1+16(x2+x+1)2)dx
=-29.lnx-1-19.1x-1+19lnx2+x+1+29.1(x+12)2+(32)2-
16.1x2+x+1+16.1((x+12)2+(32)2)2dx
=-29.lnx-1-19.1x-1+19lnx2+x+1+29.233tan-1(23x+33)-
16.1x2+x+1+16.(439tan-123x+33+2x+13x2+3x+3)
1(X3-1)2dx==-29.lnx-1-19.1x-1+19lnx2+x+1+4327tan-1(23x+33)-
16.1x2+x+1+2327tan-123x+33+118.2x+1x2+x+1
1(X3-1)2dx=-29.lnx-1-19.1x-1+19lnx2+x+1+6327tan-1(23x+33)+118.2x-
2x2+x+1
c)5x2-12(x2-6x+13)2dx
5x2-12(x2-6x+13)2=A2x-6+Bx2-6x+13+C2x-6+D(x2-6x+13)2
5x2-12=A2x-6+Bx2-6x+13+(C2x-6+D)
5x2-6x+13+152x-6+13(x2-6x+13)2dx
5(x-3)2+4dx-15x2-6x+13+13(x-32+4)2dx
5x2-12(x2-6x+13)2dx=52.tan-1(x-22)-15x2-6x+13+138(tan-1x-222+x-3x2-
6x+13)
5x2-12(x2-6x+13)2dx=5316tan-1(x-22)+18.13x-159x2-6x+13+C
d)x3(x2+2x+2)2dx
x3(x2+2x+2)2=A2X+2+Bx2+2x+2+C2X+2+E(x2+2x+2)2
(122X+2-3(x+1)2+1+2X+2+2((x+1)2+1)2)dx=12lnx2+2x+2-3tan-
1x+1+tan-1x+1+xx2+2x+2
x3(x2+2x+2)2dx=12lnx2+2x+2-2tan-1x+1+xx2+2x+2
e)dx(1+x2)4
x=tanθ;dx=secθ2dθ
reemplazando secθ2dθsecθ8=cos6θdθ
cos6θdθ=516θ+12senθcosθ+316senθcosθ(2cosθ2-1)-16(cosθsenθ)3
dx(1+x2)4=516tan-1x+12.xx2+1+316.xx2+1211+x2-1-16(xx2+1)3
dx(1+x2)4=516tan-1x+15x5+40x3+33x48x6+144x4+144x2+48+c
f)x3+x-1(x2+2)2dx
x3+x-1(x2+2)2=A2X+Bx2+2+C2X+D(x2+2)2
x3+x-1=x2+2(A2X+B)+(C2X+D)
122Xx2+2+-122X-1(x2+2)2dx=12lnx2+2+12.1x2+2-1(x2+2)2dx
x3+x-1(x2+2)2dx=12lnx2+2+12.1x2+2-(x4x2+2+28tan-1(2x2)
x3+x-1(x2+2)2dx=12lnx2+2+2-x4x2+2-28tan-1(2x2)+c
g)3x+5(2x2+x+1)2dx
h)x9(x4-1)2dx
x9(x4-1)2=x+2x5-x(x4-1)2
2x5-x(x4-1)2=Ax-1+B(X-
1)2+C(X+1)+D(X+1)2+E2X+FX2+1+G2X+H(X2+1)2
(x+38x-1+116(X-1)2+38X+1+-116X+12+-382XX2+1+182XX2+12)dx
x9(x4-1)2dx=x22+38lnx-1-116.1x-1+38lnx+1+116.1x+1-38.lnx2+1-
18.1x2+1+c
j)1(x2+9)3dx